Practical implications of ethics in AI development - Jantunen, Marianna (2020)
This Master’s thesis presents two studies: a multiple case study on perceptions and actions of AI prototype developers regarding implementation of AI ethics; and a Grey Literature review of AI ethics guidelines published by corporations, institutions and governments. The empirical study assesses the skills, practices and attitudes towards ethical dimensions of developers who create artificial intelligence applications. The results indicate that the developers have varying levels of knowledge on ethical practices; this appears to be related to the level of responsibility and rank of the developers. because information does not seem to always pass down from supervisors to lower level employees. The developers appeared to delegate responsibility of AI impacts on themselves, their supervisors and their employing institution. A framework of keywords accountability, transparency and responsibility were utilized to discover different aspects of the development. The Grey Literature review indicates that there are certain recurring themes among the studied guidelines, such as transparency, fairness, privacy and accountability, which makes the results in part consistent with the empirical research framework.